If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4 = 44 Reorder the terms: 4 + 5x = 44 Solving 4 + 5x = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5x = 44 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 44 + -4 5x = 44 + -4 Combine like terms: 44 + -4 = 40 5x = 40 Divide each side by '5'. x = 8 Simplifying x = 8
| 7g+12=9g-6 | | 3(2x-2)=4x | | 6x-1=41 | | 3(h-4)+5=60 | | 13x+2x=-150 | | 5m+42=11m | | (4x)*2=16 | | 5(8x-4)=44x | | 2-(x+5)=4x-8 | | 3(x+8)=33 | | 6(6n+7)=7(6n+6)+5 | | 7x-x=36 | | 5w+10=0 | | 6x-5y=9 | | 16(x+2)=4(4x+1)+28 | | -20y=120 | | 6x=32-2x | | 40=18x-10x | | -3(x+5)+5x=10 | | 10x^2+7x-5=0 | | 6+x=32-x | | 9x-x=40 | | 5x+2(x+8)-6(4x-5)= | | -3x^2+7x=-10 | | 8xy+6yz-4xz-8xy= | | -47-18=13a | | -1(z-6)=-20 | | -7+8x=19x+15 | | -p=2 | | -6x+9=3x-27 | | (y+3)(y+5)= | | (3b^3+9b^2-3)+(2b^3-9b+7)= |